Стереотаксический манипулятор - Синотин, А. М.; Хорошайло, Ю. Е.; Колесникова, Т. А. (ХНУРЭ, 2004)
Целью данной разработки является создание автоматизированного стереотаксического манипулятора, позволяющего практически обеспечить возможность малотравматический хирургический доступ к любым отделам мозга, используя свойства рентгеновского изображения. The stereo estimate manipulator designed for automation the worker place of doctor. The control from electric motors of manipulator and the control for the movement of a sonde makes with PC. The manipulator has a four levels of free, which a sonde movements from everything point head’s zone.
Keywords: автоматизированный стереотаксический манипулятор; медицинские технологии; малотравматическая хирургия